2013
DOI: 10.1590/1678-7757201302366
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy associated with full-mouth ultrasonic debridement in the treatment of severe chronic periodontitis: a randomized-controlled clinical trial

Abstract: Background:Photodynamic therapy (PDT) is a method of microbial reduction which can benefit periodontal treatment in areas of difficult access, such as deep pockets and furcations. The aim of this randomized controlled clinical trial was to evaluate the effects of PDT as an adjunct to full-mouth ultrasonic debridement in the treatment of severe chronic periodontitis. Material and Methods:Twenty-two patients with at least one pocket with a probing depth (PD) of ≥7 mm and one pocket with a PD of ≥5 mm and bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 27 publications
4
63
0
8
Order By: Relevance
“…Similar results were reported by many previous studies. 9,23,24,30 Our findings confirm the results of a recent study by Balata et al 36 who reported that aPDT did not add any additional effect to SRP in terms of CAL gain.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported by many previous studies. 9,23,24,30 Our findings confirm the results of a recent study by Balata et al 36 who reported that aPDT did not add any additional effect to SRP in terms of CAL gain.…”
Section: Discussionsupporting
confidence: 91%
“…In each group no statistically significant difference was observed clinically after the treatment. 25 In 2013, Souza et al studied the impacts of microbial PDT on the level of transforming growth factor (TGF) β 1 in GCF on patients. In that study they chose 50 patients with bilateral grade III furcation involvement in mandibular molars.…”
Section: S9mentioning
confidence: 99%
“…Eight out of the 18 studies have reported statistically significantly higher improvements in probing depth (PD) reduction and/or clinical attachment (CAL) gain following SRP + PDT compared to SRP alone, [21][22][23][24][25][26][27][28] _ENREF_22while the rest of 10 studies have failed to reveal statistically significant differences in these parameters. 29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers. 22,26,28,31,32 Changes of microbiological parameters were evaluated in 8 of 18 studies.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%